Recycling of Reverse Osmosis Concentrates to the Membrane Bioreactor in the MBR-RO Process for Water Reuse: effect on mbr performances - Vu, Thi Thu Nga; Montaner, Manon; Guigui, Christelle (Revue des sciences de l’eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 2017)
Wastewater effluents can be treated by an integrated membrane system combining membrane bioreactor (MBR) and reverse osmosis (RO) for effective removal of micropollutants in the field of high-quality water reuse. However, discharging the RO concentrate waste stream directly into the natural environment could lead to serious problems due to the toxic components contained in the concentrates (micropollutants, salts, organic matter). A possible solution could be the recirculation of RO concentrate waste to the MBR. However, such an operation should be studied in detail since the recirculation of non-biodegradable organic matter or high concentrations of salts and micropollutants could directly or indirectly contribute to MBR membrane fouling and modification of the biodegradation activity. In this context, the work reported here focused on the recirculation of such concentrates in an MBR, paying specific attention to MBR membrane fouling. Lab-scale experiments were performed on a continuous MBR-RO treatment line with RO concentrate recirculation. The main goal was to determine the recovery of the RO unit and of the global process that maintained good process performance in terms of biodegradation and MBR fouling. The results demonstrate that the impact of the toxic flow on activated sludge depends on the recovery of the RO step but the same trends were observed regardless of the organic matter and salt contents of the concentrates: the concentration of proteins increased slightly. Size-exclusion high performance liquid chromatography (HPLC-SEC) was employed to study the effects of RO concentrate on the production of protein-like soluble microbial products (SMPs) and demonstrated a significant peak of protein-like substances corresponding to 10-100 kDa and 100-1 000 kDa molecules in the supernatant. Thus a significant increase in the propensity for sludge fouling was observed, which could be attributed to the increased quantity of protein-like substances. Finally, the effect of the concentrate on sludge activity was studied and no significant effect was observed on biodegradation, indicating that the return of the concentrate to the MBR could be a good alternative.